2003
DOI: 10.1590/1809-4392200331104
|View full text |Cite
|
Sign up to set email alerts
|

Screening of plants found in Amazonas State for lethality towards brine shrimp

Abstract: 226 methanol and water extracts representing 74 mainly native plant species found in Amazonas State, Brazil, were tested at a standard concentration of 500 μg/mL for lethality towards larvae of the brine shrimp species Artemia franciscana.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 10 publications
1
31
0
1
Order By: Relevance
“…However, this indicates that fucoidan possessed the inhibitory and bactericidal effect against the above mentioned human bacterial pathogens. Nowadays, the brine shrimp assay is considered as an excellent method for preliminary investigations of toxicity, to several bioactive molecules from various sources (Quignard et al, 2003). Interestingly, Parra et al, (2001) reported that, the toxic effect of medicinal plants was positively correlated between the lethality to brine shrimp and the corresponding oral lethal dose in mice.…”
Section: Resultsmentioning
confidence: 99%
“…However, this indicates that fucoidan possessed the inhibitory and bactericidal effect against the above mentioned human bacterial pathogens. Nowadays, the brine shrimp assay is considered as an excellent method for preliminary investigations of toxicity, to several bioactive molecules from various sources (Quignard et al, 2003). Interestingly, Parra et al, (2001) reported that, the toxic effect of medicinal plants was positively correlated between the lethality to brine shrimp and the corresponding oral lethal dose in mice.…”
Section: Resultsmentioning
confidence: 99%
“…Dry extracts were deposited in our extract bank at the Coordenação de Pesquisas em Produtos Naturais (CPPN / INPA) where they were stored at -19 ºC. Many of these extracts were screened previously by some of us against larvae of the brine shrimp species Artemia franciscana (Quignard et al, 2003).…”
Section: Methodsmentioning
confidence: 99%
“…The aqueous fraction from ethanol extract of P. ramiflora and the aqueous extract from P. torta were toxic to A. salina (Perfeito et al, 2005). On the other hand, methanol and aqueous extracts from P. caimito bark and P. guianensis roots and wood did not presented toxicity against A. franciscana larvae (Quignard et al, 2003;Libralato et al, 2007).…”
Section: Immunomodulatory Activity and Citoxicitymentioning
confidence: 97%